Tackling school dropout through active learning: methodologies and interventions - Annoscia, Sabrina (Form@re - Open Journal per la formazione in rete, 2025)
School dropout is a complex phenomenon involving numerous individual and institutional factors. In Italy, the dropout rate, despite its improvements, is still higher than the European average, with significant regional disparities and clear gender differences. In this context, preventive policies, the quality of the education system, and the adoption of inclusive teaching methodologies all play a crucial role. In particular, the EAS method, segmented teaching, and Active Breaks can be effective in enhancing student engagement and reducing the risk of dropout, thanks to the possibility of creating personalized, gradual learning pathways and increasing students’ intrinsic motivation. To tackle school dropout and ensure a quality education for everyone, ongoing teacher training and the strengthening of the teacher-student educational relationship are both necessary. Il contrasto alla dispersione scolastica attraverso forme di apprendimento attivo: metodologie e interventi. La dispersione scolastica è un fenomeno complesso che coinvolge numerosi fattori, individuali e istituzionali. In Italia, il tasso di abbandono scolastico, seppur in miglioramento, è ancora superiore alla media europea, con disparità significative tra regioni e con nette differenze di genere. In questo scenario, le politiche preventive, la qualità del sistema educativo, e l’adozione di metodologie didattiche inclusive hanno un ruolo cruciale. In particolare, il metodo EAS, la Didattica segmentata e le pause attive (Active Breaks) possono risultare efficaci per migliorare il coinvolgimento degli studenti e ridurre il rischio di dispersione, attraverso la possibilità di generare percorsi di apprendimento personalizzati e graduali e aumentare i livelli di motivazione intrinseca degli studenti. Per contrastare la dispersione scolastica e garantire un’istruzione di qualità per tutti, risulta necessaria una formazione continua del corpo docente e il rafforzamento della relazione educativa insegnante-studenti.